2020
DOI: 10.1093/epolic/eiaa008
|View full text |Cite
|
Sign up to set email alerts
|

Learning about fiscal multipliers during the European sovereign debt crisis: evidence from a quasi-natural experiment

Abstract: Identifying fiscal multipliers, i.e. the effect of discretionary fiscal actions on growth, is challenging. It requires comparing the realisation of growth after a fiscal action to a hypothetical growth path that would have prevailed in the absence of such action. Deriving the hypothetical path usually involves very strong assumptions. This paper helps to relax some of the assumptions, using a unique new dataset on the European Commission’s recommendations under the so-called excessive deficit procedure (EDP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
(15 reference statements)
2
8
0
1
Order By: Relevance
“…The conclusions of Górnicka et al (2018) are consistent with some other analyses of the size of multipliers in the European fiscal consolidations. For example, Alesina, Favero, and Giavazzi (forthcoming) use their narrative data set of fiscal consolidation plans across OECD countries to study whether fiscal multipliers were greater in the immediate post-financial crisis years.…”
Section: Multipliers In the Wake Of The Financial Crisissupporting
confidence: 89%
See 1 more Smart Citation
“…The conclusions of Górnicka et al (2018) are consistent with some other analyses of the size of multipliers in the European fiscal consolidations. For example, Alesina, Favero, and Giavazzi (forthcoming) use their narrative data set of fiscal consolidation plans across OECD countries to study whether fiscal multipliers were greater in the immediate post-financial crisis years.…”
Section: Multipliers In the Wake Of The Financial Crisissupporting
confidence: 89%
“…They concluded that the models used by forecasters assumed values of multipliers that were too small. Górnicka et al (2018) gathered data on the forecasters' assumed values of multipliers and found that they were very low, around 0.25.…”
Section: Multipliers In the Wake Of The Financial Crisismentioning
confidence: 99%
“…Coefficient δ on the contrary increases with time, from 1.0 (for years 2010/11) to 1.2 (2010/14). Note that further specifications with different panel dimensions after the crisis for both the SB and DFE case do not alter the general picture drawn so far – quite robust estimates with general weakening of the baseline effects in later crisis years, in line with the slowdown of consolidation potential learning effects of forecasters (Górnicka et al ., ) or the end of the downturn regime…”
Section: Further Robustness Testsmentioning
confidence: 99%
“…Our findings are robust to a large set of perturbations. Yet, as a plausible qualification, we find a weakening of the effects in later crisis years, in line with the slowdown of consolidation, possible learning effects of forecasters (Górnicka et al ., ) or regime‐dependent multiplier effects (Baum, Poplawski‐Ribeiro and Weber, ; Auerbach and Gorodnichenko, ). Moreover, some Eastern European countries are influential outliers that weaken the relation to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Among the authors who have analysed this issue, Gechert, Horn, and Paetz [46] considered that the negative impact of the policies in the short-and long-term was considerably underestimated. However, Górnicka et al [47] estimated lower fiscal multipliers for European economies, contradicting the negative effect found by Gechert, Horn, and Paetz [46]. Meanwhile, Paulus, Figari, and Sutherland [48] estimated the negative effect for Greece caused by fiscal austerity measures to be 2.68% on the aggregate demand.…”
Section: Discussionmentioning
confidence: 94%